Tegafur co-crystals and methods for their preparation

CN122958402APending Publication Date: 2026-10-23LUNAN PHARMA GROUP CORPORATION
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510478632.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-16
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

[0006]综上,构型或晶型筛选并不能较好提高替加氟的疗效或降低其毒性,因此需要发展新形式的替加氟,其具有提高的溶出、溶解度和/或增加的生物利用度

Benefits of technology

[0044]本发明提供的制备的替加氟共晶的方法操作简便,制备的晶体纯度高,本发明提供的替加氟共晶晶体无论是在固态还是溶液状态下都具有较好的化学稳定性,并且具有较好的溶解性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_8
    Figure SMS_8
Patent Text Reader

Abstract

The application belongs to the technical field of pharmaceutical chemistry, and particularly relates to tegafur-3.5-dihydroxybenzoic acid co-crystal and a preparation method thereof. The new crystal form provided by the application is tegafur-3.5-dihydroxybenzoic acid co-crystal, wherein one molecule of tegafur, eight molecules of 3,5-dihydroxybenzoic acid and eleven molecules of water form a basic unit of the crystal form, and great improvement is achieved in stability, solubility and the like, the preparation method is simple in operation, good in reproducibility and suitable for industrialized production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the technical field of medicinal chemistry, specifically to tegafur-3,5-dihydroxybenzoic acid cocrystal and its preparation method. Background Technology

[0002] Tegafur, chemically named 1-(tetrahydro-2-furanyl)-5-fluoro-2,4(1H,3H)-pyrimidinidone, with the molecular formula C8H9FN2O3, is a fluorouracil derivative and a second-generation fluorouracil anti-metabolite chemotherapy drug widely used in the treatment of colorectal cancer and metastatic colorectal cancer. Its structural formula is shown below:

[0003]

[0004] Although tegafur is widely used in anti-tumor therapy, its toxicity, including severe bone marrow suppression and damage to the body, makes reducing its toxicity or improving its bioavailability a hot research topic. The literature (Chem. Pharm. Bull., Vol. 41, No. 9, 1623-1625) studied the crystal forms of tegafur and obtained four crystal forms: α, β, γ, and δ. No significant differences were found in the therapeutic effects among these crystal forms.

[0005] To improve the efficacy of tegafur, existing technologies have shown that mixing tegafur with uracil at a molar ratio of 1:4 effectively enhances its efficacy ("Cancer Investigation", Vol. 13, No. 5, 470-474). Sanchiz F et al. invented a compound formulation of tegafur, folic acid, and uracil ("Jpn. Journal Clin. Oncol.", 1994, vol. 24, No. 6, 322-326") to improve the bioavailability of tegafur. Since uracil itself has a certain degree of toxicity, Fujita H et al. pointed out that the toxicity reduction is more significant when tegafur is used in combination with thymine, adenosine, thymidine, etc. (Experimental and Clinical Pharmacotherapy, Issue 12, Riga, 1983, p. 205). US Patent 6,538,001 reports that the solubility and bioavailability of tegafur can be improved when tegafur and methyluracil form a molecular complex (i.e., a eutectic) in a 1:2 or 1:1 ratio.

[0006] In summary, configuration or crystal form screening has not been able to significantly improve the efficacy of tegafur or reduce its toxicity. Therefore, there is a need to develop new forms of tegafur with improved dissolution, solubility, and / or increased bioavailability.

[0007] Drug cocrystallization technology uses crystal engineering to co-crystallize two or more pure compounds to create new functional materials. A drug cocrystallization is defined as "a cocrystallization in which the target molecule or ion is the active pharmaceutical ingredient, and it is bonded to the cocrystallization precursor via hydrogen bonds." Drug cocrystallization is a nonionic supramolecular complex and can be used to improve physicochemical properties such as solubility, stability, and bioavailability during drug development without altering the chemical composition of the active pharmaceutical ingredient (API). This invention demonstrates that tegafur can form a cocrystallization with 3,5-dihydroxybenzoic acid as a cocrystal former (CCF), meeting these requirements and providing a basis for future selection of drug-drug cocrystallizations. Summary of the Invention

[0008] The purpose of this invention is to address the shortcomings of existing technologies by providing a cocrystal of tegafur and its preparation method, and to characterize its structure. This provides a pathway to improve the bioavailability of tegafur and reduce its toxic side effects.

[0009] A tegafur drug cocrystal, the cocrystal being composed of tegafur (I) and 3,5-dihydroxybenzoic acid (II), the structural formulas of which are as follows:

[0010]

[0011] The tegafluoride-3,5-dihydroxybenzoic acid eutectic, when subjected to Cu-Kα radiation, exhibits characteristic peaks in its X-ray diffraction pattern (denoted as 2θ) at 5.4±0.2°, 6.3±0.2°, 8.7±0.2°, 10.0±0.2°, 13.6±0.2°, 19.6±0.2°, and 19.9±0.2°.

[0012] Preferably, the tegafur-3,5-dihydroxybenzoic acid eutectic, when irradiated with Cu-Kα, exhibits characteristic peaks in its X-ray diffraction pattern (denoted as 2θ) at 10.7±0.2°, 12.9±0.2°, 16.2±0.2°, 19.0±0.2°, 20.2±0.2°, 20.4±0.2°, 23.0±0.2°, and 28.7±0.2°.

[0013] Preferably, the tegafur-3,5-dihydroxybenzoic acid eutectic, when subjected to Cu-Kα radiation, exhibits characteristic peaks conforming to the following... Figure 1 The X-ray powder diffraction pattern shown is shown.

[0014] Preferably, the crystallographic parameters of the tegafur-3,5-dihydroxybenzoic acid drug cocrystal are: triclinic crystal system, chiral space group P1; and cell parameters are: α = 96.3590(10)°, β = 107.3700(10)°, γ = 104.7850(10)°, cell volume

[0015] The second aspect of this application provides a method for preparing tegafur drug cocrystals, the specific preparation steps of which include: dissolving tegafur and 3,5-dihydroxybenzoic acid in a mixed solvent of organic solvent A and water, heating to dissolve, clarifying the solution, cooling to crystallize, filtering and drying to obtain tegafur-3,5-dihydroxybenzoic acid drug cocrystals.

[0016] The organic solvent A is selected from one or a mixture of at least two of methanol, ethanol, acetonitrile, acetone and isopropanol.

[0017] Furthermore, the organic solvent A is selected from one or two of acetonitrile, acetone, and methanol.

[0018] The molar ratio of tegafur to 3,5-dihydroxybenzoic acid is 1:1 to 5, preferably 1:3.5 to 4.5.

[0019] The mass-to-volume ratio of tegafur and organic solvent A in the system is 1:0.05-0.1, where mass is expressed in mg and volume in ml.

[0020] The volume ratio of water to organic solvent A in the system is 1:2 to 4.

[0021] The melting and heating temperature is 40–60°C.

[0022] The cooling crystallization temperature is 0–30°C, preferably 5–20°C.

[0023] The crystallization time is 45 to 72 hours.

[0024] More preferably, the preparation method includes the following steps:

[0025] Tegafur and 3,5-dihydroxybenzoic acid were dissolved in organic solvent A, and then a certain proportion of purified water was added. The mixture was heated at 40-60°C to dissolve the solution. After the solution became clear, it was cooled to 0-30°C to crystallize for 45-72 hours. The mixture was then filtered, cooled, allowed to stand, and allowed to evaporate and crystallize. The crystals were then filtered and dried to obtain a co-crystal of tegafur and 3,5-dihydroxybenzoic acid.

[0026] The drying temperature is 45–70°C, and the drying time is 8–12 hours.

[0027] A third aspect of this application provides a pharmaceutical composition comprising the tegafur and 3,5-dihydroxybenzoic acid cocrystal of the present invention, and mixed with other components.

[0028] Preferably, the pharmaceutical composition of the present invention is prepared as follows: using standard and conventional techniques, the compound of the present invention is combined with a pharmaceutically acceptable solid or liquid carrier, and optionally combined with pharmaceutically acceptable excipients and formulations to prepare a usable dosage form.

[0029] Preferably, the other components include other active ingredients, excipients, fillers, etc., that can be used in combination.

[0030] Preferably, the pharmaceutical composition is a spray, tablet, capsule, powder for injection, liquid for injection, etc.

[0031] Confirmation of crystal structure

[0032] X-ray crystal data were collected on a Rigaku XtaLAB Synergy instrument at a test temperature of 293(2) K using CuKa radiation. Data were collected in ω-scan mode and Lp correction was performed. The structure was resolved using the direct method, and all non-hydrogen atoms were identified using the difference Fourier method. Hydrogen atoms on all carbon and nitrogen atoms were obtained by theoretical hydrogenation. The structure was refined using the least squares method.

[0033] The crystallographic data obtained from testing and analyzing the tegafur crystals prepared in this invention are shown in Table 1: Its crystallographic parameters are: triclinic system, chiral space group P1; cell parameters are: α = 96.3590(10)°, β = 107.3700(10)°, γ = 104.7850(10)°, cell volume The molecular formula is C64H79FN2O46, and the molecular weight is 1631.29. The structural analysis photograph of the tegafur-3,5-dihydroxybenzoic acid eutectic crystal of this invention shows that the crystal is solvent-free, as shown in the attached image. Figure 3 As shown. The hydrogen bond diagram of the tegafur-3,5-dihydroxybenzoic acid eutectic crystal of the present invention is attached. Figure 2 As shown.

[0034] Table 1. Main crystallographic data of tegafur eutectic crystal form

[0035]

[0036] The X-ray powder diffraction testing instrument and testing conditions in this invention are as follows: X-ray powder diffractometer: PANalyticalE; Cu-Kα; sample stage: flat plate; incident light path: BBHD; diffraction light path: PLXCEL; voltage 45kV, current 40mA; divergence slit: 1 / 4; anti-scattering slit: 1; Solar slit: 0.04rad; step size: 0.5s; scanning range: 3~50°.

[0037] Based on crystallographic data, the characteristic peaks in the corresponding X-ray powder diffraction pattern (Cu-Kα) are detailed in the appendix. Figure 1 And Table 2.

[0038] Table 2. PXRD peaks of tegafur-3,5-dihydroxybenzoic acid cocrystal

[0039]

[0040]

[0041] All samples prepared in the examples have the same crystallographic parameters and X-ray powder diffraction patterns.

[0042] The TGA / DSC thermal analysis test conditions for the tegafur crystal form described in this invention are as follows: Mettler Toledo TGA / DSC thermal analyzer (model: TGA / DSC3+), dynamic temperature range: 30~300℃, heating rate: 10℃ / min, programmed gas N2, flow rate: 50ml / min, crucible: 40μl aluminum crucible.

[0043] The TGA / DSC test results of the tegafur-3,5-dihydroxybenzoic acid cocrystal prepared by the method of the present invention are as follows: Figure 4 As shown: there is a strong endothermic peak in the range of 75.97 to 99.30℃, corresponding to a weight loss of 10.4467%, which is approximately the lost bound water; there is a strong endothermic peak in the range of 223.67 to 228.12℃, which is the melting point of the tegafluoride eutectic.

[0044] The method for preparing tegafur eutectic provided by this invention is simple to operate and produces crystals with high purity. The tegafur eutectic crystals provided by this invention have good chemical stability and good solubility in both solid and solution states. Attached Figure Description

[0045] Figure 1 X-ray powder diffraction pattern of tegafur-3,5-dihydroxybenzoic acid eutectic.

[0046] Figure 2 ORTEP diagram of tegafur-3,5-dihydroxybenzoic acid eutectic.

[0047] Figure 3 Hydrogen bond diagram of tegafur-3,5-dihydroxybenzoic acid eutectic.

[0048] Figure 4 DSC-TGA image of tegafur-3,5-dihydroxybenzoic acid eutectic. Detailed Implementation

[0049] The present invention will be further illustrated by the following embodiments. It should be understood that the embodiments of the present invention are merely for illustrating the present invention and are not intended to limit the present invention. Therefore, any simple improvements to the present invention under the premise of the method of the present invention are within the scope of protection claimed by the present invention.

[0050] Example 1:

[0051] Tegafur (20.0 mg, 0.1 mmol) and 3,5-dihydroxybenzoic acid (61.6 mg, 0.4 mmol) were added to a mixed solvent of 1 ml acetone, 1.5 ml methanol, and 0.5 ml water. The mixture was heated to 60 °C and stirred under reflux for 8 hours. After slowly cooling to 5-10 °C, the mixture was allowed to stand at a controlled temperature for 48 hours to crystallize. The crystals were then filtered and dried under vacuum at 45 °C for 10 hours to obtain tegafur-3,5-dihydroxybenzoic acid eutectic with a yield of 98.6% and a purity of 99.98%.

[0052] Example 2

[0053] Tegafur (20.0 mg, 0.1 mmol) and 3,5-dihydroxybenzoic acid (15.4 mg, 0.1 mmol) were added to a mixed solvent of 1 ml acetone, 1 ml ethanol and 0.5 ml water. The mixture was heated to 40 °C and stirred for 8 hours. After slowly cooling to 5-10 °C, the mixture was allowed to stand at a controlled temperature for 48 hours to crystallize. The crystals were then filtered and dried under vacuum at 45 °C for 10 hours to obtain tegafur-3,5-dihydroxybenzoic acid eutectic with a yield of 95.6% and a purity of 99.74%.

[0054] Example 3

[0055] Tegafur (20.0 mg, 0.1 mmol) and 3,5-dihydroxybenzoic acid (77.0 mg, 0.5 mmol) were added to a mixed solvent of 2 ml acetone, 2 ml acetonitrile, and 0.5 ml water. The mixture was heated to 60 °C and stirred for 8 hours. After slowly cooling to 5-10 °C, the mixture was allowed to stand at a controlled temperature for 48 hours to crystallize. The crystals were then filtered and dried under vacuum at 45 °C for 10 hours to obtain tegafur-3,5-dihydroxybenzoic acid eutectic with a yield of 95.8% and a purity of 99.62%.

[0056] Example 5

[0057] Tegafur (20.0 mg, 0.1 mmol) and 3,5-dihydroxybenzoic acid (107.8 mg, 0.7 mmol) were added to a mixed solvent of 2.5 ml acetone, 2.5 ml acetone and 0.5 ml water. The mixture was heated to 35 °C and stirred for 8 hours. After slowly cooling to 5-10 °C, the mixture was allowed to stand at a controlled temperature for 48 hours to crystallize. The crystals were then filtered and dried under vacuum at 45 °C for 10 hours to obtain tegafur-3,5-dihydroxybenzoic acid eutectic with a yield of 89.6% and a purity of 98.98%.

[0058] 1. Light stability test

[0059] The crystal form obtained in Example 1 and the tegafluoride-1,2-bis(4-pyridyl)ethylene eutectic D1 (prepared according to method CN201980042572.7, the same below) were placed in the open for 10 days under high temperature test (60℃), high humidity test (25℃, relative humidity 90%±5%) and strong light irradiation test (illuminance 4500±500lx), and then samples were taken and the results are shown in Table 1 below.

[0060] Table 1. Results of the photostability test of tegafur crystal form

[0061] Placement conditions Placement time Example 1 D1 Properties Granular crystals Granular crystals Sample before placement 99.98% 99.92% High temperature test 10 99.97% 99.85% High humidity test 10 99.95% 99.59% Strong light irradiation experiment 10 99.96% 99.85%

[0062] Experiments showed that the purity and appearance of the tegafluoride eutectic prepared by the present invention did not change significantly under light, high temperature and high humidity conditions. However, the purity of the D1 crystal form decreased significantly under the same experimental conditions, and the impurity content increased significantly. This indicates that the crystal form prepared by the present invention has good chemical stability.

[0063] 2. Solubility test

[0064] The solubility of Examples 1 and D1 in water and solutions of different pH values ​​was determined. 10 mL of each medium (water, 0.01 mol / L HCl solution, and pH 6.8 phosphate buffer) was measured into vials, excess drug was added, the vials were sealed, and the solutions were placed in a 37°C water bath with stirring for 1 hour. The solutions were then filtered through a 2 nm filter, and the absorbance of the filtrate was measured at 200 nm to calculate the solubility of the samples. The results are shown in Table 2.

[0065] Table 2 Solubility in different media

[0066]

[0067] Solubility test results show that the tegafluoride eutectic phase prepared by this invention exhibits significantly improved solubility compared to the available crystal forms disclosed in the prior art. Further investigation revealed similar solubility test results for Examples 1-5.

[0068] 3. Dissolution rate test

[0069] This experiment was conducted in a VK7010 (Varian, USA) dissolution apparatus equipped with a VK750D heating circulator. Approximately 500 mg of sample was compressed into a 0.5 cm² disk, and a USP-certified electrically operated rotating disk was used for dissolution at a pressure of 5 tons for 5 minutes. Throughout the experiment, only one side of the disk was exposed to the solvent, and the surface area of ​​the disk remained constant. The sample was then placed in a container containing 900 mL of phosphate buffer (pH 6.8), preheated at 37°C, and stirred at 50 rpm. At regular intervals, 2 mL of sample was manually drawn. The collected samples were filtered through a 0.4 μm nylon membrane, and the calibration curves of each sample were analyzed using HPLC. The absorbance was measured at a wavelength of 271 nm in the phosphate buffer at pH 6.8.

[0070] sample <![CDATA[IDR(×10 -2 )(mg cm -2 min -1 )]]> Example 1 8.6 D1 6.4

[0071] Dissolution rate tests show that the tegafur-3,5-dihydroxybenzoic acid eutectic prepared by this invention dissolves faster than the tegafur-1,2-di(4-pyridyl)ethylene eutectic disclosed in the prior art. Examples 1-5 of this invention show similar dissolution rate test results.

[0072] 4. Hygroscopicity test

[0073] The eutectic obtained in Example 1 was used to prepare tegafur-1,2-bis(4-pyridyl)ethylene eutectic D1 according to the method of CN201980042572.7, and a hygroscopicity test was performed.

[0074] The hygroscopicity test method and conditions were based on the original experimental conditions of the General Chapter 9103 of Part IV of the Chinese Pharmacopoeia 2020: temperature 25℃±1℃, relative humidity 80%±2%. The results are shown in Table 3 below.

[0075] Among them, the description of hygroscopic characteristics and the definition of hygroscopic weight gain are as follows:

[0076] Deliquescence: The process of absorbing sufficient water to form a liquid.

[0077] Extremely hygroscopic: the weight gain due to moisture absorption is not less than 15%.

[0078] It has hygroscopic properties: the weight gain due to moisture absorption is less than 15% but not less than 2%.

[0079] Slightly hygroscopic: the weight gain due to moisture absorption is less than 2% but not less than 0.2%.

[0080] None or almost none hygroscopicity: moisture-induced weight gain less than 0.2%.

[0081] Table 3 Results of Hygroscopicity Test

[0082]

[0083]

[0084] Conclusion: The novel crystalline forms of tegafur obtained in this invention (Examples 1-5) are hygroscopic or nearly hygroscopic, and are not easily deliquescent due to high humidity, facilitating long-term storage of the drug. Furthermore, PXRD analysis of the hygroscopic crystal forms showed that each crystal form remained stable.

Claims

1. A tegafur-3,5-dihydroxybenzoic acid eutectic, characterized in that, The molar ratio of tegafur, 3,5-dihydroxybenzoic acid, and water in the crystal unit structure is 1:8:

11.

2. The cartegafluoride-3,5-dihydroxybenzoic acid eutectic according to claim 1, characterized in that, Using Cu-K α Radiation, at 2 θ The X-ray powder diffraction, expressed in terms of angle, has characteristic diffraction peaks at 5.4±0.2°, 6.3±0.2°, 8.7±0.2°, 10.0±0.2°, 13.6±0.2°, 19.6±0.2°, and 19.9±0.2°.

3. The cartegafluoride-3,5-dihydroxybenzoic acid eutectic according to claim 1, characterized in that, Using Cu-K α Radiation, at 2 θ The X-ray powder diffraction, expressed in angle, shows diffraction peaks at 10.7±0.2°, 12.9±0.2°, 16.2±0.2°, 19.0±0.2°, 20.2±0.2°, 20.4±0.2°, 23.0±0.2°, and 28.7±0.2°.

4. The cartegafluoride-3,5-dihydroxybenzoic acid eutectic according to claim 1, characterized in that, The crystal form has an X-ray powder diffraction pattern as shown in Figure 1.

5. The cartegafluoride-3,5-dihydroxybenzoic acid eutectic according to claim 1, characterized in that, Its crystallographic parameters are: triclinic system, chiral space group P1; unit cell parameters are: α = 96.3590(10)°, β = 107.3700(10)°, γ = 104.7850(10)°, cell volume 6. The method for preparing tegafur-3,5-dihydroxybenzoic acid eutectic according to any one of claims 1-5, characterized in that, The preparation method includes the following steps: dissolving tegafur and 3,5-dihydroxybenzoic acid in a mixed solvent of organic solvent A and water, heating to dissolve, clarifying the solution, cooling to crystallize, filtering and drying to obtain tegafur-3,5-dihydroxybenzoic acid drug cocrystals.

7. The method according to claim 6, characterized in that, Organic solvent A is selected from one of methanol, ethanol, acetonitrile, acetone and isopropanol.

8. The method according to claim 6, characterized in that, The molar ratio of tegafur to 3,5-dihydroxybenzoic acid is 1:1 to 5.

9. The method according to claim 6, characterized in that, The mass-to-volume ratio of tegafur to organic solvent A in the system is 1:0.05 to 0.1; the volume ratio of water to organic solvent A in the system is 1:2 to 4.

10. The method according to claim 6, characterized in that, The cooling and crystallization temperature is 0–30°C.

Citation Information

Patent Citations

  • Tegafur co-crystal

    CN114502550A

  • Crystalline modification of 5-fluoro-1-(tetrahydro-2-furyl) uracil and complex compounds based thereon, producing antineoplastic effect

    US6538001B1